An Impact of Performance of Companies with Sustainability Goal on Stock Market Movements - Shruti Nagar (European Economic Letters (EEL), 2023)
The present aims to assess the performance of the Indian companies which have adopted sustainable development goals and their impact on overall stock market movement. The study is exploratory research which is based on secondary data sources. For data analysis multiple regression model has been used. The software SPSS 26 has been utilized for the same. The study validates the impact of the performance of the companies with sustainability goal oriented approach on the overall stock market movement. It shows the progressive contribution of Indian industries towards achieving the sustainability development goals,